2011
DOI: 10.1016/j.jep.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like and neuroprotective effects of Aloysia gratissima: Investigation of involvement of l-arginine-nitric oxide-cyclic guanosine monophosphate pathway

Abstract: The present study provides convincing evidence of neuroprotection and the involvement of the l-arginine-NO-cGMP pathway in the antidepressant-like effect of AE. Therefore, AE could be of potential interest for the treatment of depressive disorders and neurological conditions associated with glutamate excitotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 61 publications
4
34
1
Order By: Relevance
“…Behavioral despair illustrates that the animal has lost the motivation to perform escape-oriented behavior (Porsolt et al 1977). TST is predicted to give less stress in animals with more pharmacological sensitivity when compared to FST (Thierry et al 1986;Zeni et al 2011). In this test, animals show vigorous activity followed by progressive periods of immobility, aimed at rescuing themselves from the unpleasant situation termed helplessness.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral despair illustrates that the animal has lost the motivation to perform escape-oriented behavior (Porsolt et al 1977). TST is predicted to give less stress in animals with more pharmacological sensitivity when compared to FST (Thierry et al 1986;Zeni et al 2011). In this test, animals show vigorous activity followed by progressive periods of immobility, aimed at rescuing themselves from the unpleasant situation termed helplessness.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen minutes later, mice were submitted to the TST or open-field test. The experimental protocols for NMDA and d-serine administrations were selected on the basis of previous results from our laboratory Ludka et al 2013;Kaster et al 2012;Moretti et al 2011;Rieger et al 2014;Zeni et al 2011;Zomkowski et al 2010Zomkowski et al , 2012 and others (Wlaz et al 2011).…”
Section: Involvement Of Nmda Receptors In the Anti-immobility Effect mentioning
confidence: 99%
“…Mice were submitted to behavioral testing 60 min later. The dose of MK-801 was chosen based on previous studies Kaster et al 2012;Ludka et al 2013;Moretti et al 2012;Zeni et al 2011;Zomkowski et al 2012). In another set of experiments, mice were administered with creatine (0.01 mg/kg, po) or vehicle.…”
Section: Involvement Of Nmda Receptors In the Anti-immobility Effect mentioning
confidence: 99%
“…6 Recently, Zeni et al 7 demonstrated that Aloysia gratissima's aqueous extract has both antidepressant-like and neuroprotective effects in mice.…”
Section: Introductionmentioning
confidence: 99%